PENGARUH PENGUMUMAN PEMBERLAKUAN LARANGAN EKSPOR MINERAL DAN BATU BARA (MINERBA) MENTAH TERHADAP REAKSI PASAR SAHAM SEKTOR PERTAMBANGAN - Zubaidah, Dyah Dwi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study is to see the effects of banned on the export of unprocessed minerals and coal towards the reactions of mining sector in stock market. Market reaction can be seen from stock movement of Trading Volume Activity (TVA) and Abnormal Return (AR) before and after the policy. Period of this research is 30 days before and 30 days after this policy is happen. 38 samples is from all of the mining enterprise that is on the list in BEI and active in trading during the period of this study. This study use Paired Sample T-Test to see the difference of Trading Volume Activity and Wilcoxon Signed Rank Test for Abnormal Return. The result explain that there is no significance difference in Trading Volume Activity and Abnormal Return between period of before and after this policy.Keyword : Trading Volume Activity, Abnormal Return, banned on the export of unprocessed minerals and coal policy